Stereoselective metabolism of donepezil and steady-state plasma concentrations of S-donepezil based on CYP2D6 polymorphisms in the therapeutic responses of Han Chinese patients with Alzheimer's disease - Jin Lu; Lili Wan; Yuan Zhong; Qi Yu; Yonglong Han; Pengguo Chen; Beiyun Wang; Wei Li; Ya Miao; Cheng Guo (Elsevier, 2015)
The therapeutic response rates of patients to donepezil vary from 20% to 60%, one of the reasons is their genetic differences in donepezil-metabolizing enzymes, which directly influence liver metabolism. However, the mechanism of donepezil metabolism and that of its enantiomers is unknown. This study evaluated CYP2D6 polymorphisms to elucidate the stereoselective metabolism of donepezil and to confirm the association between the steady-state plasma concentrations of the pharmaco-effective S-donepezil and the therapeutic responses of Han Chinese patients with Alzheimer's disease. The in vitro study of the stereoselective metabolism demonstrated that CYP2D6 is the predominant P450 enzyme that metabolizes donepezil and that different CYP2D6 alleles differentially affect donepezil enantiomers metabolism. A total of 77 Han Chinese patients with Alzheimer's disease were recruited to confirm these results, by measuring their steady-state plasma concentrations of S-donepezil. The related CYP2D6 genes were genotyped. Plasma concentrations of S-donepezil (based on CYP2D6 polymorphisms) were significantly associated with therapeutic responses. This finding suggests that plasma concentrations of S-donepezil influence therapeutic outcomes following treatment with donepezil in Han Chinese patients with Alzheimer's disease. Therefore, determining a patient's steady-state plasma concentration of S-donepezil in combination with their CYP2D6 genotype might be useful for clinically monitoring the therapeutic efficacy of donepezil.